1986
DOI: 10.1093/sleep/9.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Slow Wave Sleep: Considerations from a Clinical Viewpoint

Abstract: Summary: Previous experimental observations, almost exclusively carried out with young healthy subjects, have been interpreted as showing a particular restorative role for human slow wave sleep (SWS). This article considers whether findings from polygraphic sleep studies in patients and elderly subjects lead to similar inferences about the meaning or "function" of SWS. The question was approached in three different ways: (a) by presenting results from a long-term study in elderly subjects whose SWS data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…As a single descriptive feature, the reduction of SWS lacks specificity, since it may occur in a large variety of medical, neurological and psychiatric conditions [23], However the phenomenon may have different physiopathologic significances. In generalized anxiety it proba bly represents an epiphenomenon resulting from the reduction and fragmentation of sleep, but in dysthymia it is not associated with any features of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…As a single descriptive feature, the reduction of SWS lacks specificity, since it may occur in a large variety of medical, neurological and psychiatric conditions [23], However the phenomenon may have different physiopathologic significances. In generalized anxiety it proba bly represents an epiphenomenon resulting from the reduction and fragmentation of sleep, but in dysthymia it is not associated with any features of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Gillberg & Åkerstedt 42) suggested that total sleep time might be more important for neurobehavioral performance than the amount of SWS. Therefore, studies investigating the relationship between SWS and neurobehavioral functions have produced inconsistent findings [42][43][44] . The purpose of the present study was to test the following three hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…27 In contrast, 2 studies did not find evidence for a potential association between personality traits and sleep architecture. 28,29 The association between perfectionism and sleep architecture has not been investigated so far. Thus, our study addresses this gap in the literature.…”
mentioning
confidence: 99%